The relationship of microcirculation parameters of the bulbar conjunctiva and coronary angiography in patients with coronary artery disease - N. V. Korneeva; B. Z. Syrotin; N. V. Bondar; V. Ya. Rudman (Российский кардиологический журнал)
Aim. To identify the associations between microcirculation parameters obtained using the method of bulbar conjunctiva videobiomicroscopy and coronary angiography in patients with acute coronary syndrome (ACS).Material and methods. Fifty six patients with ACS underwent coronary angiography (CAG) and on days 7-10 of hospitalization — bulbar conjunctiva videobiomicroscopy. A comparison of micro- and macrocirculation parameters by methods of pair and canonical correlations has been carried out.Results. Multiple positive and negative correlations of the average force between microcirculation parameters (arteriolar-venular ratio (AVR), capillary number per 1 mm2 of conjunctival surface, intravascular erythrocyte aggregation in the eye corner) conjunctival areas) and severity of coronary sclerosis. By the method of canonical correlations, strong (r=0,71), positive statistically significant (p=0,0256) correlation was observed.Conclusion. Bulbar conjunctiva videobiomicroscopy can be used as non-invasive screening to identify individuals with a high risk of coronary sclerosis. Thus, the following parameters can be used: AVR, capillary number per 1 mm2 of conjunctival surface, intravascular erythrocyte aggregation in the eye corner and the number of conjunctival areas with identified intravascular erythrocyte aggregation. In case of low AVR values (0,2-0,3), reduction of the capillary bloodflow (reducing of the capillary number less than 4 units/mm2 of the conjunctival surface) and widespread intravascular erythrocyte aggregation in three and four areas of the bulbar conjunctiva, patients should underwent CAG because of high risk of coronary atherosclerosis.